Effect of First Aid Choking Education for Child Aged 1-5 Years on Parents Knowledge - Astilia, Astilia (Sahabat Publikasi Kuu, 2024)
Choking is an emergency due to blockage of the upper airways by food or other objects that requires immediate action, so mothers need to be educated in providing first aid to prevent morbidity and mortality in children. This study aims to determine the effect of first aid education regarding poisoning emergencies in children aged 1-5 years in Kanagarian Pematang Panjang, Sijunjung. The type of research used is experimental with a one group pretest-posttest research design. The total sample was 30 people with purposive sampling technique. The SPSS data analysis used was the Wilcoxon test to see the effect before and after being given education. The results of the research showed that mothers' knowledge after being given education about eating emergencies increased the most, namely 20 people with a p value of 0.000 < 0.05, which means that there was an influence of education about eating emergencies for children 1-5 years old on mothers' knowledge in Kanagarian Pematang Panjang, Sijunjung District. . Providing education increases the mother's knowledge and makes the mother know, understand and hopefully be able to apply any known information regarding first aid for toddlers aged 1-5 years.